Salmonella typhimurium ghosts vaccine: The promising enhanced link between immunity modulation and colorectal cancer induced in albino rats - Rana Abdul Hamza Al-Qarraawi; Hiyame Abdul Ridha Al –Awade (International Journal of Medical Toxicology and Legal Medicine, 2025)
Despite the remarkable medical progress in cancer treatment, colorectal cancer remains one of the most diagnosed types and a major cause of death worldwide. This has demand for the development of new, more effective and selective techniques against cancer cells, including immunotherapy using bacteria such as therapeutic bacterial vaccines characterized by their ability to target cancer cells by disrupting immune tolerance within the tumor microenvironment and stimulating a long-term immune response. Therefore, the current study aimed to investigate the therapeutic role of Salmonellatyphimurium ghosts (STGs) vaccine to reduce the effect of Azoxymethane (AOM)-induced colorectal cancer in male albino rats (Rattusrattus), which were used as a model to achieve the required tests, which included two axes: the first axis included evaluating the safety of the locally prepared vaccine (which was prepared using critical chemical concentrations in the sponge-like reduced protocol) and applying the full experimental vaccination program, in addition to studying the effect of the vaccination program on the invasiveness of S. typhimurium by studying the immune response of vaccinated rats and comparing it with the results of the vaccine evaluation for unvaccinated rats, the second axis included investigating the immunomodulatory activity of the vaccine prepared on rats induced with colorectal cancer (before, during and after treatment with the full STGs vaccination program) by measuring the expression level of the immune biomarker Programmed death ligand - 1 (PDL-1), which is a transmembrane protein that acts as a ligand for the immune checkpoint receptor PD-1. It was concluded that the S. typhimurium ghost vaccine (STGs) has an important role as an immune stimulating factor in the body to activate systemic cytokine-secreting T cells, thus recruiting both the innate and acquired immune response for the purpose of improving or modifying the tumor-specific immune response, and as a promising tool for the treatment of colon cancer.